O sentido do (ser) docente com a tecnologia digital pelo olhar da fenomenologia existencial: um estudo sobre as práticas de professores em uma perspectiva interdisciplinar - Melo, Israela Míriam de (Universidade Federal Rural do Semi-Árido, 2018)
In this dissertation, we seek to understand, phenomenologically, how the relationship of teaching practice with digital technology comes from the experiences lived by teachers in the school institutional context. The participants of this research are teachers of the Basic Education network who, as post-graduate students, participated in a broad sense course in Interdisciplinary Education. The work follows a qualitative approach, whose methodology is based on the phenomenological-existentialist approach of the philosopher Martin Heidegger, through which we seek to understand, interpret and analyze the manifestations of meaning that were being revealed in the field of this study, especially about the involvement between the (being) teachers, interdisciplinarity and digital technologies. In order to compose the theoretical network, we also dialogue with other authors who, in their writings, bring a phenomenological perspective on the proposed subject. We highlight here the studies of Paulo Freire, whose ideas understand dialogue as the essence of a liberating and humanistic education. Because it is a phenomenological research, we adopt a flexible methodological course, presenting, therefore, the non-linearity that it exposes in the field. In this way, we used as methodological strategies the conversation wheel, held in three meetings with the participating teachers. Then we transcribe the dialogues recorded during the conversation wheel. We perform the analysis of these narratives, initially seeking to describe the autonomous experiences of teachers on their practices with digital technologies, in order to perceive the meaning of teacher / technology interaction. In the second moment, based on an interpretative analysis, we aim to understand how the relation between teacher and technology is given in the context of the narrated experiences. Among the results, we verified that the practices of teachers with digital technologies reveal experiences that transcend the prescribed curriculum of the specialization course, also indicating the transdisciplinarity, since they reveal, in their narratives, experiences in contexts that are not limited only to the institutional scope school. In dealing with educational practices with technologies, teachers perceive both the relevance they have in the learning process of their students and in the unveiling of possibilities that result in manifestations of care with one another and in emotions, such as fear and contentment. In addition, it was possible to verify that the relation of the teachers with the digital technology also happens of experiences lived throughout their lives, and they are significant. Thus, they point out the importance of training courses for their teaching practice, however, do not consider them as determinants, since they believe that this must start from the desire and autonomy of the teacher, always seeking new knowledge and reinventions of their practices with digital technologies. From this perspective, from an eminently phenomenological-existential approach, this work allowed us to reflect on what it is like to be an interdisciplinary teacher with digital technologies: it can be understood as an act of educational protagonism beyond the institutional school context, not considering digital technologies as mere technical objects, but rather as means used for purposes other than their productions, being an educator who, with the aid of digital technology, performs educational, pedagogical and curricular teaching practices, still seeking new projects and actions to re-signify their practices with technologies
Keywords: Docência; Interdisciplinaridade; Tecnologia digital; Fenomenologia-existencial; Teaching; Interdisciplinary; Digital Technology; Existenctial-phenomenology; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES